VARIABILITY OF THE MAIN AGRONOMIC VALUABLE TRAITS OF MOUNTAIN SAVORY (SATUREJA MONTANA L.) IN «BOBRIK» VARIETIES - I. T. Ushakova; L. V. Bespalko; V. A. Kharchenko; A. V. Molchanova; G. D. Levko (Овощи России, 2019)
In recent years, interest in mountain savory is increasing and this is due to the rich biochemical composition, useful properties and decorative qualities of this plant. The materials were sortopopulyatsiya savory mountain. The study was conducted in the open ground in Moscow region (2012-2018) on experimental plots of the laboratory green, spicy taste and floral crops of FSBSI FSVC. The work on improving the source material by applying individual selection, the most aligned with economically valuable traits form ЧГ32-12 with high potential productivity of inflorescences and green mass, decorative, flavour and hardiness. Conducted testing and pre-multiplication of promising accessions, which was transferred into the "GOSSORTKOMISSIA" in 2018 called “Bobrik”. The yield of green increased in vegetation years in the first year of vegetation was 0,650 kg/m2, in the second – 3.0 kg/m2, and in the third year reached 5.4 kg/m2. Indicator sign "plant height" increased over the years of vegetation (11.4 cm, 25.5 cm and 40.2 cm, respectively). The values of the sign "number of shoots" in the first year of vegetation was 11.6 PCs., in the second year – sharply increased (255.1 PCs.), in the third year – reached its maximum (787.3). The accumulation of dry matter in the years of vegetation increased: the first year contained 20.08%; the second year – 26.95%; and the third year of vegetation – 29.71%. The content of ascorbic acid in the flowering phase in the second year of vegetation increased compared to the first year (8.21 mg/% and 5.87 mg (%). The amount of water-soluble antioxidants in the second year of the growing season has increased almost two times in comparison with the first year (to 22.7 mg/g and AAE 42.39 mg/g of AAE), in the third year there is a decrease in rate – 28.6 mg/g of AAE. Thus, the green of the mountain variety "Bobrik" is a source of biologically active substances, such as ascorbic acid and carotenoids, so the culture can be recommended for the use of young shoots and leaves in fresh and dry form, as a seasoning for salads, sauces, marinades, meat and fish dishes, as well as spicy and aromatic additives for the preparation of drinks.